RF Technologies for Future Colliders - Belomestnykh, Sergey (Frontiers in Physics, 2022)
Particle colliders remain indispensable scientific instruments to discover and study new elementary particles and fundamental forces of nature. Whether the collider is a factory (used to improve precision of measuring properties of already discovered particles or to enable studies of rare decay channels), an energy frontier machine (aimed at discovering new particles and forces), a heavy ion collider (allowing studies of what the universe looked like in the early moments after its creation), or an electron-hadron collider (where electrons are used for probing heavy ions or protons to study the fundamental force binding all visible matter), the radio frequency technologies play a key role in enabling the machine to reach its goals. This article considers challenges presented to the radio frequency technologies by the next generation of particle colliders and reviews R&D approaches and directions to address these challenges.